Choosing Our Future : A Practical Politics of the Environment - Taylor, Ann 1947- (London Routledge, 1992)
Britain's first ever Cabinet-level politician with specific responsibility for the environment lays out her practical manifesto for tackling some of today's most pressing crises. The focus is on cooperation and on empowering the community.
Include Index
Keywords: Economic development--Environmental aspects -- Environmental protection -- Human ecology